Maternal shift work during pregnancy and biomarkers of reproductive function among the male offspring - a pilot follow-up study - Cecilia Høst Ramlau-Hansen; Linn Berger Håkonsen; Maria Christensen; Jens Peter Bonde; Jørn Olsen; Ane Marie Thulstrup (Nordic Association of Occupational Safety and Health (NOROSH), 2011)
OBJECTIVES: The aim of this study was to examine the associations between maternal shift work during pregnancy and measures of semen quantity and quality and level of reproductive hormones among young, adult men. METHODS: From a Danish pregnancy cohort established in 1984-1987, 347 sons aged 18-21 years were selected in 2005-2006 and semen and blood samples were taken. At around the 36^th week of gestation, the mothers completed a questionnaire that included a question on shift work during pregnancy. Information on shift work was available for mothers of 278 sons. RESULTS: Of the 278 sons, 42 (15%) had had fetal exposure to maternal shift work. Men exposed to maternal shift work had 30% [95% confidence interval (95% CI) -58-16] lower adjusted percentage normal morphology sperm, 18% (95% CI -30-100) higher adjusted sperm concentration, and 11% (95% CI -0.6-25) higher adjusted levels of testosterone than men not exposed. Adjusted semen volume, total sperm count, percentage motile sperm and serum levels of estradiol, follicle stimulation hormone (FSH), luteinizing hormone (LH), inhibin B, and sex hormone-binding globulin (SHBG) were not associated with maternal shift work during pregnancy. CONCLUSIONS: The results of this pilot study indicate no strong associations between maternal shift work during pregnancy and the quantity and quality of semen or level of reproductive hormones among sons.